2007
DOI: 10.1139/h07-117
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, capillary blood glucose, and activity level of activity-restricted, hospitalized, pregnant women in the third trimester: a pilot study

Abstract: Activity restriction in hospital is commonly prescribed by care providers to decrease the incidence of maternal or fetal morbidity in high-risk pregnancies. The purpose of this pilot descriptive study was to collect preliminary data on dietary intake, capillary blood glucose concentrations, and activity level in high-risk, activity-restricted, pregnant women in the third trimester of pregnancy. Dietary food intake records, capillary blood glucose, and daily pedometer step totals were investigated in 20 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…During pregnancy (before hospitalization in the AR women), both groups reported a similar physical activity pattern in METÁhr/week. However, during hospitalization and AR, the mean daily total step count was only 1,503.5 + 1,377.4 steps/day, similar to the mean step count reported in our previous study for 16 AR pregnant women in the third trimester (1,579 + 936 steps/day; Tomkins et al, 2007) and significantly less than the step count reported for 19 AM women of the same gestational age (6,495 + 2,282 steps/day). After reviewing the evidence related to public health issues, Tudor-Locke and Bassett (2004) proposed classifications for pedometer-determined physical activity in healthy adults, suggesting <5,000 steps/day as an index for a sedentary lifestyle.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…During pregnancy (before hospitalization in the AR women), both groups reported a similar physical activity pattern in METÁhr/week. However, during hospitalization and AR, the mean daily total step count was only 1,503.5 + 1,377.4 steps/day, similar to the mean step count reported in our previous study for 16 AR pregnant women in the third trimester (1,579 + 936 steps/day; Tomkins et al, 2007) and significantly less than the step count reported for 19 AM women of the same gestational age (6,495 + 2,282 steps/day). After reviewing the evidence related to public health issues, Tudor-Locke and Bassett (2004) proposed classifications for pedometer-determined physical activity in healthy adults, suggesting <5,000 steps/day as an index for a sedentary lifestyle.…”
Section: Discussionsupporting
confidence: 89%
“…We have used pedometer assessment previously and have found step counts to be a reliable measure of physical activity in this population (Tomkins, Mottola, & Giroux, 2007). Participants reset the pedometer to 0 upon awaking in the morning and recorded total daily steps at the end of each day.…”
Section: Pedometer and Pedometer Logmentioning
confidence: 99%
See 3 more Smart Citations